2014
DOI: 10.1068/p7805
|View full text |Cite
|
Sign up to set email alerts
|

What Affects Facing Direction in Human Facial Profile Drawing? A Meta-Analytic Inquiry

Abstract: Two meta-analyses were conducted to examine two potential sources of spatial orientation biases in human profile drawings by brain-intact individuals. The first examined profile facing direction as function of hand used to draw. The second examined profile facing direction in relation to directional scanning biases related to reading/writing habits. Results of the first meta-analysis, based on 27 study samples with 4171 participants, showed that leftward facing of profiles (from the viewer's perspective) was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
(47 reference statements)
1
13
0
9
Order By: Relevance
“…Therefore, faces that turn to the left appear to be more familiar than faces in the opposite direction. Although this disposition has been replicated as a whole, which cheek is put forward is affected by various factors, including the model's gender [22], professions [28,29], expressive intention [30,31], painter's handedness [13,17,32], and reading habits [32,33]. Because faces are processed by specialized neural mechanisms, the findings on face processing may not be applicable to more general visual processing [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, faces that turn to the left appear to be more familiar than faces in the opposite direction. Although this disposition has been replicated as a whole, which cheek is put forward is affected by various factors, including the model's gender [22], professions [28,29], expressive intention [30,31], painter's handedness [13,17,32], and reading habits [32,33]. Because faces are processed by specialized neural mechanisms, the findings on face processing may not be applicable to more general visual processing [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies of art books and catalogs, there is evidence suggesting that artists prefer poses showing left cheeks when composing a portrait, but showing right cheeks when composing their own self-portraits ( LaBar, 1973 ; McManus and Humphrey, 1973 ; Latto, 1996 ; Nicholls et al, 1999 ; Suitner and Maas, 2007 ; Powell and Schirillo, 2009 ; Tosun and Vaid, 2014 ). It has been suggested that both biases may in fact originate from a preference for showing one’s left cheek, as self-portraits are most typically painted while watching oneself in a mirror.…”
Section: Introductionmentioning
confidence: 99%
“…An early study documenting this effect was first reported by Vaid and Singh (1989) in the context of a chimeric faces affect judgment task whereby left to right readers reported that faces with a left-sided smile appeared happier while right to left readers reported that faces with a right-sided smile seemed happier; this finding has been replicated by Sakhuja, Gupta, Singh, and Vaid (1996) and Eviatar (1997). The effect of reading/writing direction has also been reported in the direction of drawing vehicles or animals (Vaid, 1995) or human facial profiles (Tosun & Vaid, 2014), and in the placement in space of symmetrical figures (Faghihi et al., 2019). A reading/writing direction effect has also been noted in tasks involving speeded dot production proceeding in different directions (Vaid, 1998), in line length estimation (Singh, Vaid, & Sakhuja, 2000), line bisection (Chokron & Imbert, 1993), figure perception in the orientation of published drawings and pictures (Lee & Oh, 2016), aesthetic judgments of motion trajectories (Friedrich et al., 2014; Maass, Pagani, & Berta, 2007), and even in number representation (for a review, see Göbel, Shaki, & Fischer, 2011; Núñez, 2011).…”
Section: Reading/writing Direction Effectmentioning
confidence: 83%
“…Previous work has shown that outward-directed limb movements are executed with greater ease than inward-directed movements (Dreman, 1974), a reflection of a biomechanical principle referred to as chirality effect (Vaid, 2011). Indeed, many studies have shown a chirality effect whereby right-handers prefer to execute left-to-right strokes when drawing with their right hand (see De Agostini & Chokron, 2002; Tosun & Vaid, 2014; van Sommers, 1984). A study by Viggiano and Vannucci (2002) showed that when drawing objects with implied movement (animals, vehicles), right-handers faced the objects leftward while left-handers faced them rightward, consistent with biomechanical biases for outward-directed strokes.…”
Section: Biomechanical Influence Related To Hand Preferencementioning
confidence: 99%